Mitigation of DIS flooding attacks in RPL‐based 6LoWPAN networks. Issue 2 (13th December 2019) - Verma, Abhishek; Ranga, Virender
Abstract: The IPv6 Routing Protocol for Low‐Power and Lossy Networks (RPL) is the de facto routing protocol for IPv6‐based Low‐Power Wireless Personal Area Networks (6LoWPAN). In RPL protocol, DODAG Information Solicitation (DIS) messages are sent by the node to join the network. A malicious node can exploit this mechanism to send illegitimate DIS messages to the neighbor nodes to perform a DIS flooding attack. In this research paper, it is observed that the DIS flooding attack increases the control packet overhead of the network, which significantly degrades the network's performance. This further increases the power consumption of the nodes in the network. To address this problem, a mitigation scheme named Secure‐RPL is proposed. The proposed scheme mitigates significantly the effects of DIS flooding attack on the network's performance. The effectiveness of the proposed Secure‐RPL scheme is compared with standard RPL protocol. The experimental results show that Secure‐RPL detects and mitigates DIS flooding attack quickly and efficiently in both static and dynamic network scenarios, without adding any significant overhead to the nodes. Abstract : In this paper, it is observed that the DIS flooding attack increases the control packet overhead of the network, which significantly degrades the networks performance. To address this problem, a mitigation scheme named Secure‐RPL is proposed. Secure‐RPL mitigates significantly the effects of DIS flooding attack on the network's performance. The experimental results show that Secure‐RPL detects and mitigates DIS flooding attack quickly and efficiently in both static and dynamic network scenarios, without adding any significant overhead to the nodes.